P-65 Project ECHO™: programme management of a disruptive innovation – project managers' perspective. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - McTernaghan, Tracey; Webb, Hazel
Abstract : Background: Project ECHO™ (Extension for Community Healthcare Outcomes) is a tele-mentoring programme that uses video-conferencing technology to share evidence-based knowledge, best practice and education by using case-based learning. Hospice UK's strategic plan is to extend the reach of hospice care (Hospice UK, 2017), with the Project ECHO™ model being identified as vehicle of innovation and a methodology to achieve this. Engagement with hospices throughout the United Kingdom commenced in 2017 and by April 2018, Hospice UK delivered its first three-day training programme 'Immersion Training' to two hospices. As of June 2019 a further 15 hospices have completed this training programme in either London or Belfast. The Hospice UK Project Managers for the Project ECHO™ programme, based in London and Belfast, support the operational delivery of the training programme. With additional organisational support from a Programme Management working group, consisting of clinical, finance, ICT, governance, communication and fundraising staff. Aim: To examine the experiences and tools used by the Project Managers to deliver the Hospice UK Project ECHO™ Programme. Method: The Project Managers developed and implemented the following successful tools: Project plan; pre-training support tools/guidelines which hospices use to establish 'readiness' to commit to training; operation/programme management guidelines; stakeholder analysis; issue log; fortnightly operational meetings (to map activity against key milestones). Results: The Project Managers have established successes and challenges: Success: staff appointed whose sole focus is to manage the Project ECHO™ programme. Engagement with hospices who have thoroughly analysed the 'strategic fit' of Project ECHO™ by using the pre–training support tools/guidelines; Challenges: recommended key personnel to include, a champion, a facilitator, an admin/co–ordinator and IT support, who do not attend training. Conclusions: The Hospice UK Project ECHO™ continues to develop its programme management tools to meet the demands of its customers.